2005
DOI: 10.2308/acch.2005.19.3.123
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Expertise of CFOs and Accounting Restatements

Abstract: We investigate whether the characteristics of chief financial officers (CFOs) are associated with accounting errors (using accounting restatements as a proxy). We investigate several metrics of financial literacy similar to those suggested for members of audit committees by the NYSE-NASD Blue Ribbon Committee. These metrics include years of work as a CFO, experience at another company, advanced degrees (like M.B.A.s), and professional certification (like a CPA). We use a logit model to test whether the likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
2
27

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(262 citation statements)
references
References 13 publications
13
201
2
27
Order By: Relevance
“…2 Factors related to the management and corporate governance characteristics, including the financial expertise of the CFOs (Aier et al, 2005); diffuse ownership of the firms (Defond and Jiamblavo, 1991); Manager's conservative attitudes (Hay and Sandefur, 2007); the adoption of aggressive accounting policies as a result of capital market pressures (Richardson et al, 2002), and managers' demand for meeting industry standards as well as the income or sale estimations of the market analysts.…”
Section: Future Restatements and Abafeementioning
confidence: 99%
See 2 more Smart Citations
“…2 Factors related to the management and corporate governance characteristics, including the financial expertise of the CFOs (Aier et al, 2005); diffuse ownership of the firms (Defond and Jiamblavo, 1991); Manager's conservative attitudes (Hay and Sandefur, 2007); the adoption of aggressive accounting policies as a result of capital market pressures (Richardson et al, 2002), and managers' demand for meeting industry standards as well as the income or sale estimations of the market analysts.…”
Section: Future Restatements and Abafeementioning
confidence: 99%
“…Indeed, the authors show that a restatement, having removed some uncertainty about the firm's earnings, might actually create additional uncertainty about the remaining financial statements, and the perceived credibility and competence of management. In a comparative study conducted by Aier et al (2005), the financial statements of restating and non-restating companies matched on year, industry and company size were analysed. Specifically, the authors' results suggest that companies whose CFOs have more job experience as CFOs, MBAs, and CPAs are significantly less likely to restate their earnings.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, classification management involves the re-classification of financial statement items for the purpose of enhancing certain performance measures, such as core earnings, without changing bottom-line net income. 2 Account manipulation to improve the perception of the firm has been extensively discussed and researched. 3 Classification smoothing was the focus of McVay's (2006) research which showed that managers will shift expenses out of operating income to more transitory "special items."…”
Section: Introductionmentioning
confidence: 99%
“…As a company grows they may need to seek out financial experts because of the lack of in house financial expertise (Aier et al 2005). We use change in total assets to -37 -proxy for growth (GR).…”
Section: Ltamentioning
confidence: 99%